AYURVEDIC MANAGEMENT OF ECZEMA (VICHARCHIKA) - A REVIEW - Neelam, *Arya; Anita, Sharma; V. K., Gothecha; Rohit Kumar, Khatik (International Journal of Ayurveda and Pharma Research, 2016)
In the Ayurvedic text all skin diseases were included under the Kushtarog. Which is classified in two divisions i.e. Mahakushta and Kshudrakushta. Vicharchika is described under Kshudrakushta. The clinical presentation of Vicharchika similar to Eczema in modern dermatology. Eczema (also called atopic dermatitis) is characterized by dry itchy skin with areas of poorly demarcated erythema and scale. In the acute phase eczema may be vesicular and oozing, in the chronic phase it may become hyperpigmented and lichenified (thickened). Excoriations (scratch marks) are frequently seen. The modern science has greatly advanced, particularly in dermatology but there is no specific medicaments for sure cure of eczema but symptomatic treatments like steroids are used, but they produce serious side effects like nephrotoxicity, osteoporosis, skin cancer etc. Modern pharmacology whole body. It brings a balance of body, mind and spirit. Ayurveda believes that All Dosha in balance is essential for well-being. offers treatment for the symptom of eczema. However, it does not provide treatment for the root. Therefore, recurrence is very common. Ayurveda offers treatment for the root of eczema by cleansing vitiated Dosha and balancing the Dosha and Dhatus.